2002
DOI: 10.1021/tx000267b
|View full text |Cite
|
Sign up to set email alerts
|

Microsome-Mediated Oxidation of N-Nitrosodiethanolamine (NDELA), a Bident Carcinogen

Abstract: N-Nitrosodiethanolamine (NDELA), an environmentally prevalent, potent carcinogen, undergoes competitive rat liver microsome-mediated oxidation at both the alpha (adjacent to N)- and beta-positions of the 2-hydroxyethyl chains. The former process, alpha-hydroxylation, is detected by the formation of glycolaldehyde (determined as its 2,4-dinitrophenylhydrazone DNP) that is assumed to arise from the decomposition of the corresponding alpha-hydroxynitrosamine, which is also the progenitor of the 2-hydroxyethyldiaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 57 publications
2
39
0
1
Order By: Relevance
“…NDELA is a bident carcinogen that undergoes competitive rat liver microsome-mediated oxidation at both the a (adjacent to N)-and b-positions of the 2-hydroxyl chains as illustrated in Scheme 1 [38,39]. These are the two positions ''alerted'' by the bond contributions given below.…”
Section: Chemico-biological Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…NDELA is a bident carcinogen that undergoes competitive rat liver microsome-mediated oxidation at both the a (adjacent to N)-and b-positions of the 2-hydroxyl chains as illustrated in Scheme 1 [38,39]. These are the two positions ''alerted'' by the bond contributions given below.…”
Section: Chemico-biological Observationsmentioning
confidence: 99%
“…These are the two positions ''alerted'' by the bond contributions given below. NHMOR (N-nitrosoethylethanalamine) (see Scheme 1) has been observed to generate glyoxal-deoxyguanosine in DNA both in vitro and in vivo [39].…”
Section: Chemico-biological Observationsmentioning
confidence: 99%
“…Deuterium isotope effects have been used extensively in the study of the mechanisms of nitrosamine-induced carcinogenesis (18,(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82). The first experiment to utilize deuterium substitution in the study of nitrosamineinduced cancer demonstrated that perdeuteration of NDMA lowered the liver carcinogenicity of this compound in rats (65).…”
Section: (4r)-[4-2 H 1 ]Nnk Was Less Tumorigenic Than Nnk and (4s)-[4mentioning
confidence: 99%
“…The first experiment to utilize deuterium substitution in the study of nitrosamineinduced cancer demonstrated that perdeuteration of NDMA lowered the liver carcinogenicity of this compound in rats (65). Subsequent work with NDMA and other nitrosamines showed that biological and KIEs could also be observed on levels of DNA adducts (18,73,78,81) and rates of metabolism, respectively (66,69,71,73,74,77,79,82). In the metabolism work, however, several conflicting results have been obtained.…”
Section: (4r)-[4-2 H 1 ]Nnk Was Less Tumorigenic Than Nnk and (4s)-[4mentioning
confidence: 99%
“…This is in contrast to acyclic nitrosamines such as N-nitrosodiethylamine which produce separate aldehyde and diazohydroxide products upon α-hydroxylation. The presence of two electrophilic centers in a molecule such as 4 results in a more complex pattern of DNA adduct formation than observed with acyclic nitrosamines, and is reminiscent of the bident carcinogens described by Loeppky, although in that case adduct formation results from two separate electrophiles generated from the same molecule (47). Thirteen dGuo adducts of α-acetoxyNPYR have been previously identified, and some of these result, directly or indirectly, from reactions at both electrophilic centers (31).…”
Section: Discussionmentioning
confidence: 95%